Study on Damage Constitutive Model of High-Concentration Cemented Backfill in Coal Mine. (29th October 2021) - Yang, Baogui; Yang, Haigang
Abstract : In order to construct the damage constitutive model (DCM) of high-concentration cemented backfill (HCCB) in coal mine, the generalized Hoek-Brown strength criterion was used as the failure criterion. For the difference of theoretical derivation of constitutive relation, a new DCM based on residual strength was proposed. Combined with the conventional triaxial compression test, the correctness and rationality of the DCM were verified. The damage evolution characteristics of HCCB were analyzed, and the physical meaning of model parameters was clarified. The results show that (a) the theoretical curves of stress-strain relation are in good agreement with its experimental curves, which means DCM can simulate the deformation and failure process of HCCB. (b) The damage evolution curve of HCCB is S -shaped. To some extent, the confining pressure can inhibit the development of damage. (c) The parameter F 0 reflects the position of the peak point of the DCM, and parameter n is the slope of the straight line segment in the postpeak strain softening stage, which are, respectively, used to characterize the strength level and brittleness of HCCB. The establishment of DCM of HCCB is helpful to reveal its deformation and failure mechanism and provides theoretical basis for its strength design.